The Effect of Mind Mapping Integrated Problem Based Learning (PBL) Learning Strategies on Learning Outcomes in Biodiversity & Plantae Topics - Erlina Erlina (Jurnal Pendidikan Biologi, 2023)
Learning Strategy Problem Based Learning (PBL) is a learning strategy that develops students' critical thinking skills through solving real-world problems. This study aims to determine the effect of learning through a Problem-Based Learning strategy integrated with Mind Mapping on students' Biology learning outcomes. This research was conducted at SMA Negeri 1 Merbau using a pre-test and post-test control group design. Data from the pre-test and post-test results were analyzed by looking at the N-Grain Score, followed by the ANACOVA test and continued with the parameter estimate test. The Anacova test was carried out to determine the influence of the mind mapping integrated PBL learning model on student learning outcomes. Therefore, a follow-up test was carried out: a parameter estimate test showing Class A (PBL-mind mapping) = 21.582, Class B (PBL) = 21.505 and control class = 0. PBL integrated Mind Mapping has a very significant effect on students' cognitive learning outcomes.